2021
DOI: 10.3390/foods10040802
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Way Analysis Coupled with Near-Infrared Spectroscopy in Food Industry: Models and Applications

Abstract: Near-infrared spectroscopy (NIRS) is a fast and powerful analytical tool in the food industry. As an advanced chemometrics tool, a multi-way analysis shows great potential for solving a wide range of food problems and analyzing complex spectroscopic data. This paper describes the representative multi-way models which were used for analyzing NIRS data, as well as the advances, advantages and limitations of different multi-way models. The applications of a multi-way analysis in NIRS for the food industry in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…As well, [44] applied PETIS technology to study the effect of light on H 2 15 O flow in rice plants. Where found that the plants were exposed to low light, the H 2 15 O flow was activated more slowly. By the same token, [45] studied the visualize of 15 O-water flow in tomato and rice plants in light and darkness by using PETIS technology.…”
Section: Gamma Rays Imagingmentioning
confidence: 98%
See 4 more Smart Citations
“…As well, [44] applied PETIS technology to study the effect of light on H 2 15 O flow in rice plants. Where found that the plants were exposed to low light, the H 2 15 O flow was activated more slowly. By the same token, [45] studied the visualize of 15 O-water flow in tomato and rice plants in light and darkness by using PETIS technology.…”
Section: Gamma Rays Imagingmentioning
confidence: 98%
“…Where found that the plants were exposed to low light, the H 2 15 O flow was activated more slowly. By the same token, [45] studied the visualize of 15 O-water flow in tomato and rice plants in light and darkness by using PETIS technology. Although the applications of Gamma-ray imaging techniques are mainly used for research and development purposes, it has extremely great potential to serve as a tool for the development of several operations in the agriculture and food sectors.…”
Section: Gamma Rays Imagingmentioning
confidence: 98%
See 3 more Smart Citations